Factor IX - Furie, Bruce (Henry Stewart Talks, 2007)
Factor IX, Blood coagulation, Thrombus formation, Factor IX gene, Vitamin Kdependent proteins and gamma-carboxyglutamic acid, Factor IX: biochemistry and structure, Hemophilia B
Reviewed at 2015/09/29